Delayed Aortic Stent Collapse in Blunt Traumatic Aortic Injury Repair - Alhaizaey, Abdullah; Aljabri, Badr; Alghamdi, Musaad; AlAhmari, Ali; Abulyazied, Ahmed; Asiry, Mohammed; Al-Omran, Mohammed (AORTA, 2019)
Background Endovascular stent grafting has emerged as an option to treat traumatic aorta injuries with reported significantly low mortality and morbidity. Stent collapse is one of the complications that can occur in this type of treatment. The aim of this article is to analyze the expected cause of stent collapse and to draw attention to the importance of the surveillance follow-up, as this phenomenon may occur late postdeployment.Methods A retrospectively collected dataset from the two highest volume trauma centers in Saudi Arabia was analyzed between April 2007 and October 2012. A total of 66 patients received stent grafts for traumatic aortic injury and were included in the study. We apply Ishimaru's anatomical aortic arch zones and Benjamin's aortic injury grading systems. There were 35 patients with aortic injury at zone 2, 26 patients in zone 3, and 5 patients in zone 4. About 96% (63) of the injuries were grades 2 and 3, including large intimal flap or aortic wall pseudoaneurysm with change in wall contour. The technical success rate, as defined by complete exclusion of lesions without leaks, stroke, arm ischemia or stent-related complications, was 90%.Results Proximal stent collapse occurred in 4.5% of patients (3 of 66 inserted stents) during follow-up of 4 to 8 years (mean, 6 years). Patients with stent collapse tended to have an acute aortic arch angle with long-intraluminal stent lip, when compared with patients with noncollapsed stents. Intraluminal lip protrusion more than 10-mm increased collapse (p < 0.001). Stent-grafts sizes larger than 28 mm also demonstrated a higher collapse rate (p < 0.001).Conclusions The risk of stent collapse appears related to poor apposition of the stent due to severe aortic arch angulation in young patients and to large stent sizes (>28 mm). Such age groups may have more anatomical and aortic size changes during the growth. Clinical and radiological surveillance is essential in follow-up after stent-graft treatment for traumatic aortic injury.
Keywords: aortic stent; traumatic aorta; stent collapse; thoracic aorta